Legal Research Methodology Reposition in Research on Social Science - Budianto, Agus (International Journal of Criminology and Sociology, 2022)
A legal researcher must see that research is an activity. The research is not only reading books, principles, doctrines, and regulations but also an activity to find data. Legal research should no longer distinguish between normative research and sociological research, or qualitative and quantitative research. This research method uses focus group discussions as used in qualitative research. The results of the study are that the law was born from the community that the legal system consists of substance, system, and culture. So that legal research that has its characteristics and is different from social science (sui generis) needs to be re-examined in its meaning in research. Related to the use of primary data existence, in socio-legal research requires primary data whose ranking consists of 7 (seven), namely: Dissertation, National and International scientific journal articles, Thesis and Thesis, Interview, Academic Paper, Court Verdict and Case, which how to obtain primary data must be systematic, scientific and rational. So in addition to normative juridical research with the object of research on legal principles, teachings or legal theories, and legal doctrines, legal research needs to reposition primary data in socio-legal research.